Człowiek zmediatyzowany - Adamski, Andrzej (Studia Theologica Varsaviensia, 2018)
The Mediatized Man - Summary The media are gaining to be more and more important in human life. They appropriate larger and larger areas of it. It is difficult to us to live without them. This situation causes social, cultural, but also psychic changes. Numerous attempts of integration man with virtual reality on a neuronal level raise question: We have new anthropological breakthrough or rather the end of anthropology?